ANALISIS PENDEKATAN MALCOLM BALDRIGE CRITERIA FOR PERFORMANCE EXCELLENCE (MBCfPE) TERHADAP KINERJA DI PT. KINENTA INDONESIA - Susanto, Edi (Jurnal Sistem Teknik Industri, 2017)
The purpose of this research is to implement a self-assessment through a survey on the overaallperformance measurement approuach Malcolm Baldrige Kriteria for Performance Excellent namely on sevencriteria : leadership, strategi planning, customer fokus, measurement, analysis, and knowledge management,workforce focus, operation fokus and results to determine the level of performance in PT. Kinenta Indonesia.The research data was obtained from interviews, observations, questionnaires and literature. Then analyzedwith the provisions of the assessment criteria MBCfPE. Thus obtained from the survey results MBCfPE withtotal points 784 points. Then in accordance with the scores level at posisu MBCfPE PT. Kinenta Indonesiaperformance Benchmark Leader with Excellent category.